Rapid access to t-butylalkylated olefins enabled by Ni-catalyzed intermolecular regio- and trans-selective cross-electrophile t-butylalkylation of alkynes. Issue 17 (12th April 2022) - Zhan, Yi-Zhou; Meng, Huan; Shu, Wei
Abstract : A direct reductive cross-dialkylation of alkynes is achieved to afford trans -dialkylated olefins using two distinct alkyl bromides. The reaction undergoes with exclusive chemo-, regio- and stereoselectivity without the use of organometallic reagents. Abstract : Among the carbo-difunctionalization of alkynes, the stereoselective dialkylation of alkynes is the most challenging transformation due to associated competitive side reactions and thus remains underdeveloped. Herein, we report the first Ni-catalyzed regio- and trans -selective cross-dialkylation of alkynes with two distinct alkyl bromides to afford olefins with two aliphatic substituents. The reductive conditions circumvent the use of organometallic reagents, enabling the cross-dialkylation process to occur at room temperature from two different alkyl bromides. This operationally simple protocol provides a straightforward and practical access to a wide range of stereodefined dialkylated olefins with broad functional group tolerance from easily available starting materials.